Improving Students’ Engagement Using Collaborative Canva Storyboard - Deonisia Tyas Yuniawati; Joko Priyana (Universitas Muhammadiyah Yogyakarta, 2024)
Implementing the Collaborative Canva Storyboard will equip the students with integrated skills. However, some people have not recognized Collaborative Canva Storyboard as a way to improve students’ engagement in classroom activities. This study explores a lecturer's experiences and challenges in using Collaborative Canva Storyboard and identifies how Collaborative Canva Storyboard would be implemented to enhance university students' engagement and integrate 4Cs skills. Under the design of action research, the study was conducted in four stages: reconnaissance, planning, action and observation, and reflection. The study involved 45 undergraduate students in an Accounting Education Department taking English classes in their first semester. Based on the results of students' interviews and students' work, the use of Collaborative Canva Storyboard can be a means to improve students’ engagement. In addition, the study found that Collaborative Canva Storyboards were beneficial for building up students’ communication, collaboration, creativity, and critical thinking skills.